Parents' dilemma: A therapeutic decision for children with spinal muscular atrophy (SMA) type 1 - Boursange, Sophie; Araneda, Marco; Stalens, Caroline; Desguerre, Isabelle; Barnerias, Christine; Nougues, Marie-Christine; Isapof, Arnaud; Quijano-Roy, Susana; Blu Genestine, Nadia; Ouillade, Laetitia; Martinez Jalilie, Maripaz; Castiglioni, Claudia; et al. (Frontiers in Pediatrics, 2022)
Background: SMA type 1 is a severe neurodegenerative disorder that, in the absence of curative treatment, leads to death before 1 year of age without ventilatory support. Three innovative therapies are available to increase life expectancy. Purpose: i) to increase knowledge about parents’ experiences with their decision to have opted for an innovative therapy; ii) to assess the middle-term psychological consequences in the parents’ lives. Methods: We used an in-depth interview; a self-administrated questionnaire and self-report scales (BDI-II, STAI-Y, PSI-SF, SOC-13, PBA, DAS 16 and FICD). We compared parents “hesitant” before the decision to parents who were not-hesitant and the group of parents whose child was treated with gene therapy (GT) to parents whose child received another innovative therapy. Main results: We included n=18 parents of 13 children. Parent’s mean age was 34.7 (± 5.2), child’s average age was 44.3 months (± 38.0). Retrospectively, most parents felt involved by doctors in decision-making on treatment, they felt their point of view was considered and were satisfied with the effects of the treatment. The group of parents "non-hesitant" was more depressed (p<0.001), more anxious (p=0.022) and had higher parental stress (p=0.026) than the group of "hesitant” parents; the group of "GT-treated" parents was more depressed (p=0.036) than the group of parents with "other therapy". Qualitative data highlights revealed: the need to save the child's life at all costs; the fear of coping with end of life and palliative care, the high value of perceived physician confidence in the treatment, the hope that the child will acquire autonomy or be cured. At the time of the decision, no parents felt they fully understood all of the issues regarding therapy and the disease. Conclusion: Hesitating before making a decision did not predispose parents to depression and anxiety. The narratives suggest that the parents faced a dilemma regarding their child's health in an urgent context. The decision was not final, and parents will continue to think about it throughout the care process.